Return on Investment in Alternative Markets: The Case of The Polish Rare Book Market - Lukasz ZAKONNIK; Piotr CZERWONKA (Communications of International Proceedings, 2022)
In the presented article, the authors pose the question - how profitable it is to invest in the rare book market? The study was conducted on the Polish market. Polish-language old biblical books published in the years 1561-1839 were established as the research group. The article used primary statistical methods and presented the so-called average annual rate of return on investment in rare books in Poland. The article indicated that the average annual rate of return (adjusted for inflation) was, in most cases, a few percent (about 3-5%). Thus, the return on investment is not very large but allows to effectively cope with inflation.
Keywords: art market; investing; rate of return; rare books; alternative markets; bible